Information communications technologies and academic libraries in the knowledge economy - Zhou, Tinashe G.; Ruvinga, Caroline; Zhou, Munyaradzi; Musungwini, Samuel (Journal of International Academic Research for Multidisciplinary, 2016)
Using a case study of a library in Zimbabwe, the purpose of the research was to establish how Information Communication Technologies (ICTs) were being used to enhance Knowledge Management practices at the library. This included establishing the perceptions of the library staff concerning KM and knowledge sharing practices prevalent at the library. The ICT infrastructure in place was assessed in terms of adequacy, information literacy skills and provision of information and internet services to users. The research revealed that KM was a concept not well understood at the library. Participants are open to the idea of sharing knowledge but cited lack of trust concerning other people’s knowledge, lack of motivation to support knowledge sharing initiatives and lack of proper organizational guidelines on sharing as challenges affecting knowledge sharing initiatives. The ICT infrastructure was deemed not adequate and problems to do with bandwidth were cited. It is recommended that KM workshops and seminars be conducted to enlighten members on the idea, an incentive system should be put in place to motivate members to share knowledge and a separate bandwidth be dedicated specifically for the library.